2021
DOI: 10.3389/fneur.2021.629325
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Rowland Universal Dementia Assessment Scale for the Detection of Mild Cognitive Impairment and Dementia in a Diverse Cohort of Illiterate Persons From Rural Communities in Peru

Abstract: Background: The accurate diagnosis of neurocognitive disorders in illiterate Peruvian populations is challenging, largely owing to scarcity of brief cognitive screening tools (BCST) validated in these diverse populations. The Peruvian version of the Rowland Universal Dementia Assessment Scale (RUDAS-PE) is a BCST that relies minimally on educational attainment and has shown good diagnostic accuracy in an urban illiterate population in Peru, yet its psychometric properties in illiterate populations in rural set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
(40 reference statements)
1
10
0
1
Order By: Relevance
“…Similar results we found in our previous study (9) in two culturally distinct cohorts of illiterate subjects from two rural communities in the jungle of Peru (Santa Clotilde y Chuquibambilla), who compared to illiterate persons from de city of Lima, they performed signi cantly worse on the same both cognitive domains of the Q-RUDAS, suggesting that educational level, unspeci ed sociocultural or linguistic factors present in rural environments may in uence performance on the Q-RUDAS in illiterate persons.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar results we found in our previous study (9) in two culturally distinct cohorts of illiterate subjects from two rural communities in the jungle of Peru (Santa Clotilde y Chuquibambilla), who compared to illiterate persons from de city of Lima, they performed signi cantly worse on the same both cognitive domains of the Q-RUDAS, suggesting that educational level, unspeci ed sociocultural or linguistic factors present in rural environments may in uence performance on the Q-RUDAS in illiterate persons.…”
Section: Discussionsupporting
confidence: 88%
“…Although several studies reported an effect of limited (< 7 years) or no formal education on RUDAS scores, which some studies suggest to be speci c to the visuo-spatial construction and Praxis items (7)(8)(9), this generally did not affect diagnostic performance when the cutoff value was lowered by one or two points in these participants. An advantage of the RUDAS across LMIC and HIC settings appear to be its suitability for dementia screening in populations with limited or no formal education.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…In this order of ideas, the PT would meet the conditions to be administered to detect CD and dementia in elderly people with a low educational level or illiterate through TNP. This would be the first study that supports the use of PT through the TNP in LA, although the computerized version of the RUDAS 65 was recently analyzed in Peru and reported adequate psychometric indicators to discriminate CD and dementia in populations with heterogeneous educational levels, illiterate, and rural 19,62,63 . This is pioneering research in LA, although it has some limitations.…”
Section: Dement Neuropsycholmentioning
confidence: 92%
“…Por otro lado, Custodio et al (12) señalan que la versión peruana de la Escala Universal de Evaluación de Demencia de Rowland (RUDAS-PE) es una BCST que se basa mínimamente en el nivel educativo y ha demostrado una buena precisión diagnóstica en una población analfabeta urbana en Perú, sin embargo, sus propiedades psicométricas en poblaciones analfabetas en entornos rurales del Perú país no han sido investigados previamente, llegando a la conclusión que el RUDAS-PE tiene propiedades psicométricas aceptables y se desempeñó bien en su capacidad para discriminar DCL y demencia en dos cohortes de adultos mayores analfabetos de dos comunidades rurales peruanas distintas.…”
Section: Validación O Adaptación De La Escala De Evaluación Sobre Los...unclassified